A Joint Experimental and Theoretical Study on the Nanomorphology of CaWO4 Crystals - Longo, Valeria M. [UNESP]; Gracia, Lourdes; Stroppa, Daniel G.; Cavalcante, Laecio S. [UNESP]; Orlandi, Marcelo [UNESP]; Ramirez, Antonio J.; Leite, Edson R. [UNESP]; Andres, Juan; Beltran, Armando; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Amer Chemical Soc, 2011)
By the joint use of experimental techniques such as field emission scanning electron microscopy (FEG-SEM), transmission electron microscopy (TEM), and high resolution transmission electron microscopy (HR-TEM) and ab initio theoretical calculations on the slabs surface energy with application of the Wulff construction was performed to study the shape of CaWO4 nanocrystals obtained by a microwave assisted hydrothermal (MAN) method. Under equilibrium conditions, the shape is a slightly truncated tetragonal bipyramid enclosed with eight isosceles trapezoidal surfaces of (101) (Ca-terminated) and two top squares of (001) (O-terminated). Calculated band structures and densities of states are analyzed to find the electronic structures of the different surfaces. The more pronounced elongation of the (001) facet of the experimental FIG with respect to the theoretical prediction results from the favorable interaction between hydroxyl anions and Ca exposed atoms of this surface.